A comparative report on the spatial distribution and density of dinoflagellate cysts in surface sediments of Cancabato Bay, Tacloban City - Sumalinog, Troy B.; Yap-Dejeto, Leni G. (2024)
Dinoflagellate cysts are a resistant inoculum source for harmful algal blooms. HAB events linked to cysts have been documented in various regions of the Philippines, including Cancabato Bay in Eastern Visayas. The only data of cysts from the bay were collected from 2014 to carly 2015. An updated assessment is thus warranted. This study reevaluated the distribution and abundance of dinoflagellate cysts in Cancabato Bay in 2023. Analysis of surface sediment samples (0-2 cm) across 17 stations via sieving and palynological techniques identified 21 species of dinoflagellate cysts. Cyst densities ranged from 16-84 cysts/g DW across all stations, which were significantly higher (p-1.78x105) than the total cyst densities recorded from samples collected in 2014-15. Higher cyst densities were observed in the muddy sediments of the bay's inner region, while lower densities were from stations closer to the sandy mouth of the bay. Cysts of Pyrodinium bahamense (Polysphaeridium zoharyi) were detected across 11 stations, while Alexandrium sp. cysts, which were not found in 2014-15, were observed in 15 stations. The average P. bahamense cyst density was highest in station C14 at 12 cysts/g DW, lower than the highest density (16 cysts/g DW) observed from the previous study for the same species. As in the 2014-15 samples, cyst density in the 2023 samples may have been influenced by the muddy composition and organic content of the sediments, and by pH and current velocity of the surface waters. The rise in total cyst density compared to the previous study could stem from limited sediment resuspension in the inner bay area and the persistent abundance of vegetative cells in the water column.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.